Analisis Strategi Pemasaran Pada Café Purnama Di Kecamatan Polewali, Kabupaten Polewali Mandar - Rosmini, Rosmini; Safitri, Nursan; Suhab , Resky Faradibah (Institut Agama Islam Negeri Parepare, 2025)
This study aims to analyze the marketing strategies of Café Purnama in Polewali District, Polewali Mandar Regency. The method used is descriptive qualitative with data collected through interviews, observations, and documentation. The results of the study indicate that Café Purnama's strengths lie in its superior quality of local coffee, strategic location, comfortable and aesthetic atmosphere, friendly service, and complete supporting facilities. However, weaknesses were found in the aspects of promotional strategies that have not been optimized, limited workforce during peak hours, an unstructured ordering system, and a lack of menu innovation. The business opportunities include the increasing demand for hangout spaces among youth and digital workers, as well as the potential for collaboration with local communities. The threats faced involve competition with other cafés that implement more aggressive promotions and have larger seating capacities. This study concludes that Café Purnama has significant potential to grow if it is able to develop more structured and innovative promotional strategies.